Muhammadiyah Java and the Cultural Foundation for Progressive Islam - Erizal Erizal; Metriadi Metriadi; Zidni Ilman Nafi'an; Mursal Mursal; Ahmad Lahmi (Jurnal Kajian dan Pengembangan Umat, 2026)
This article analyzes the role of Javanese cultural foundations in shaping Muhammadiyah’s concept of Progressive Islam (Islam Berkemajuan). As a reformist Islamic movement in Indonesia, Muhammadiyah has consistently emphasized the purification of Islamic teachings alongside efforts toward social transformation through education, health services, and community empowerment. In the Javanese context, however, this reformist orientation encounters a complex cultural environment characterized by strong local traditions, an emphasis on social harmony, and symbolic religious expressions that continue to shape communal life.This study employs a qualitative literature-based approach by examining relevant scholarly works, Muhammadiyah official documents, and contemporary studies published between 2022 and 2025. The analysis focuses on how Muhammadiyah in Java engages with local culture through rationality, social ethics, and Islamic humanism. The findings demonstrate that Muhammadiyah does not adopt a confrontational stance toward Javanese culture. Instead, it applies a strategy of selective cultural accommodation by integrating cultural elements compatible with Islamic principles while critically reinterpreting practices considered inconsistent with its reformist vision.The study further shows that Islam Berkemajuan functions not only as a theological framework but also as a practical cultural paradigm that enables Muhammadiyah to balance doctrinal consistency with social adaptability. Through cultural da‘wah, educational institutions, and social service programs, Muhammadiyah in Java promotes a rational, ethical, and humanistic model of Islam that supports religious moderation and social progress. This article contributes to Islamic studies by highlighting the importance of cultural engagement in sustaining moderate Islamic movements within culturally plural societies.Keywords: Muhammadiyah, Javanese Culture, Progressive Islam, Cultural Foundation, Religious Moderation